Problem-Based Audio-Visual Animation Media for Indonesian Language Learning in Elementary Schools - Faris Deniarrais Suhanda; Gusti Ayu Putu Sukma Trisna; Dewa Gede Firstia Wirabrata (Jurnal Edutech Undiksha, 2024)
Learning media that utilizes digital technology has not been fully utilized optimally so that students feel bored and less enthusiastic about using learning media that only relies on books, especially when learning Indonesian. Based on these problems, it is necessary to develop animated learning media that can accommodate students to be more active and enthusiastic in learning. This research aims to develop a learning media in the form of problem-based audio-visual animations on the sub-theme of togetherness in elementary school Indonesian language content houses. The development of problem-based audio-visual animation refers to the procedures contained in the ADDIE model, namely: analysis, design, development, implementation and evaluation. However, the stages carried out in this research only reached the development stage. The subjects in this research were audio-visual animations which were assessed by 2 material experts, 2 media experts, 2 design experts, 1 teacher and 12 students. The object of this research is the validity of audio-visual animation. The data collection process was carried out using a questionnaire method using a Likert scale. Data analysis was carried out using a percentage formula. The percentage results obtained from material expert, media expert, design expert, teacher and student responses were respectively 95.83%, 93.74%, 88.54%, 92.21% and 93.74% with very good qualifications. Thus, it can be concluded that this problem-based audio-visual animation is feasible and valid for use in the learning process.